Asteriscus graveolens exhibits Antihypertensive Activity through Activation of Vascular KATP Channels Activation in Rats - El-Ouady, Fadwa; Eddouks, Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Objective: The objective of the study was to evaluate the antihypertensive activity of Asteriscus graveolens. Methods: L-NAME hypertensive and normotensive rats have received orally the aqueous extract of Asteriscus graveolens aerial parts (AGAPE) (100 mg/kg) during six hours for the acute experiment and during seven days for the sub-chronic treatment. Thereafter, blood pressure parameters were evaluated. Concerning the in vitro investigation, the vasorelaxant effect of AGAPE was tested in isolated thoracic aortic rings. Results: AGAPE extract significantly decreased the blood pressure parameters in hypertensive rats. Moreover, the results revealed that AGAPE exhibited antihypertensive effect through its vasorelaxant properties. More interestingly, this vasorelaxant activity seems to be probably mediated through activation of K+ ATP-sensitive (KATP) channels. Conclusion: The study demonstrates the antihypertensive activity of aqueous Asteriscus graveolens extract in hypertensive rats through activation of vascular KATP channels. This finding supports the use of this plant for the management of hypertension in Morocco.
Keywords: aqueous extract